Recombinant vaccinia viruses expressing GP46/M-2 protect against Leishmania infection. - McMahon-Pratt, D (1993)
Leishmania is a genus of parasitic protozoa capable of causing a spectrum of human diseases. The GP46/M-2 membrane glycoprotein has been demonstrated in a murine model system to elicit a protective immune response against infection with Leishmania amazonensis; in highly susceptible BALB/c mice, immunization leads to significant protection against infection. In the present study, for induction of long-term immunological effects, two recombinant vaccinia viruses, derived from the wild type and attenuated variant 48-7 and expressing the GP46/M-2 protein, were constructed; to ensure safety, we used the attenuated vaccinia virus mutant (48-7) as a live vector. Susceptible BALB/c mice immunized with either GP46/M-2-recombinant vaccinia virus were significantly protected against infection with L. amazonensis; 45 to 76% of the animals were completely protected (sterile) against a challenge inoculum of 10(3) infective organisms. The protectively immunized animals demonstrated T- and B-cell-dependent immunological responses; both lymphokine responses as well as antibody responses and long-term memory are indicative of T-cell activation. This first report of the use of a recombinant vaccinia virus to induce protection against a Leishmania infection indicates that recombinant vaccinia viruses should be of value in the design of a safe and effective vaccine against this parasitic disease.